Expression of human GLUD1 and GLUD2 glutamate dehydrogenases in steroid producing tissues. (5th November 2015) - Spanaki, Cleanthe; Kotzamani, Dimitra; Petraki, Zoe; Drakos, Elias; Plaitakis, Andreas
Abstract: Besides the housekeeping glutamate dehydrogenase1 (hGDH1), humans have acquired, via a recent duplication event, a hGDH2 isoenzyme with distinct functional properties and tissue expression profile. GDH catalyzes the reversible deamination of glutamate to α-ketoglutarate while reducing NAD(P) to NAD(P)H. As the generated NADPH can be used in bio-synthetic pathways, we studied here the expression of hGDH1 and hGDH2 in human steroidogenic tissues using specific antibodies. Results revealed high levels of hGDH1 and hGDH2 expression in steroid-producing cells in all tissues studied. While the cellular expression pattern of the two proteins was similar for the adrenal cortex, it was distinct for testis, ovaries and placenta. Functional analyses revealed that steroid hormones interacted differentially with the two isoenzymes. As synthesis of steroid hormones requires NADPH, expression of hGDH1 and hGDH2 in steroidogenic cells may serve their particular metabolic needs. Highlights: Both hGDH1 and hGDH2 are expressed in human steroidogenic tissues. hGDH1 and hGDH2 expression localizes to steroid-synthesizing cells of steroidogenic organs. Steroid hormones interact with hGDH2 with a greater affinity than with hGDH1. hGDH2 expression may serve particular metabolic needs of steroidogenic organs.